Bladder Regeneration Using a Polycaprolactone Scaffold with a Gradient Structure and Growth Factors in a Partially Cystectomized Rat Model - Kim, Ho Yong; Chun, So Young; Lee, Eun Hye; Kim, Bomi; Ha, Yun-Sok; Chung, Jae-Wook; Lee, Jun Nyung; Kim, Bum Soo; Oh, Se Heang; Kwon, Tae Gyun (Journal of Korean medical science, 2020)
Tissue engineering can be used for bladder augmentation. However, conventional scaffolds result in fibrosis and graft shrinkage. This study applied an alternative polycaprolactone (PCL)-based scaffold (diameter = 5 mm) with a noble gradient structure and growth factors (GFs) (epidermal growth factor, vascular endothelial growth factor, and basic fibroblast growth factor) to enhance bladder tissue regeneration in a rat model.BACKGROUNDTissue engineering can be used for bladder augmentation. However, conventional scaffolds result in fibrosis and graft shrinkage. This study applied an alternative polycaprolactone (PCL)-based scaffold (diameter = 5 mm) with a noble gradient structure and growth factors (GFs) (epidermal growth factor, vascular endothelial growth factor, and basic fibroblast growth factor) to enhance bladder tissue regeneration in a rat model.Partially excised urinary bladders of 5-week-old male Slc:SD rats were reconstructed with the scaffold (scaffold group) or the scaffold combined with GFs (GF group) and compared with sham-operated (control group) and untreated rats (partial cystectomy group). Evaluations of bladder volume, histology, immunohistochemistry (IHC), and molecular markers were performed at 4, 8, and 12 weeks after operation.METHODSPartially excised urinary bladders of 5-week-old male Slc:SD rats were reconstructed with the scaffold (scaffold group) or the scaffold combined with GFs (GF group) and compared with sham-operated (control group) and untreated rats (partial cystectomy group). Evaluations of bladder volume, histology, immunohistochemistry (IHC), and molecular markers were performed at 4, 8, and 12 weeks after operation.The bladder volumes of the scaffold and GF group recovered to the normal range, and those of the GF group showed more enhanced augmentation. Histological evaluations revealed that the GF group showed more organized urothelial lining, dense extracellular matrix, frequent angiogenesis, and enhanced smooth muscle bundle regeneration than the scaffold group. IHC for α-smooth muscle actin, pan-cytokeratin, α-bungarotoxin, and CD8 revealed that the GF group showed high formation of smooth muscle, blood vessel, urothelium, neuromuscular junction and low immunogenicity. Concordantly, real-time polymerase chain reaction experiments revealed that the GF group showed a higher expression of transcripts associated with smooth muscle and urothelial differentiation. In a 6-month in vivo safety analysis, the GF group showed normal histology.RESULTSThe bladder volumes of the scaffold and GF group recovered to the normal range, and those of the GF group showed more enhanced augmentation. Histological evaluations revealed that the GF group showed more organized urothelial lining, dense extracellular matrix, frequent angiogenesis, and enhanced smooth muscle bundle regeneration than the scaffold group. IHC for α-smooth muscle actin, pan-cytokeratin, α-bungarotoxin, and CD8 revealed that the GF group showed high formation of smooth muscle, blood vessel, urothelium, neuromuscular junction and low immunogenicity. Concordantly, real-time polymerase chain reaction experiments revealed that the GF group showed a higher expression of transcripts associated with smooth muscle and urothelial differentiation. In a 6-month in vivo safety analysis, the GF group showed normal histology.This study showed that a PCL scaffold with a gradient structure incorporating GFs improved bladder regeneration functionally and histologically.CONCLUSIONThis study showed that a PCL scaffold with a gradient structure incorporating GFs improved bladder regeneration functionally and histologically.